Multirate Layered Space-Time Coding and Successive Interference Cancellation Receivers in Quasi-Static Fading Channels - Sellathurai, M.; Ratnarajah, T.; Guinand, P. (IEEE transactions on wireless communications, 2007)
We investigate the performance of multirate layered space-time coded MIMO systems with successive decoding and interference cancellation (SDIC) receivers in quasi-static Rayleigh fading channels. The proposed framework can be viewed as a class of diagonal layered space-time coded system with each of the layers is encoded independently with different rates subject to equal per-layer outage probabilities. We derive the probability density functions of the per-layer mutual informations, which can be used to estimate the per-layer rates. Using these densities we show that the proposed transceiver increases the outage capacity. We also present simulation results illustrating the outage capacity performance for a variety of transmit and receive antenna combinations and the associated near optimal per-layer rates of input signals. In particular we show that for sufficiently large numbers of transmit and receive antennas, the system can achieve near capacity in quasi-static fading environments. Based on these results, multirate codes are designed using punctured turbo codes and simulation results show significant gains in packet error-rate (PER) performances compared to that of V-BLAST architectures with lower receiver complexities.